Evolutionary Histories of Camellia japonica and Camellia rusticana - Harue Abe; Saneyoshi Ueno; Ayumi Matsuo; Shun K. Hirota; Hiroki Miura; Mong‐Huai Su; Yun‐Guang Shen; Yoshihiko Tsumura; Yoshihisa Suyama; Zhong‐Lang Wang (Ecology and Evolution)
ABSTRACT The genus Camellia is widely distributed, primarily in East Asia. Camellia japonica is located at the northern limit of this genus distribution, and understanding changes in its distribution is crucial for understanding the evolution of plants in this region, as well as their relationship with geological history and climate change. Moreover, the classification of sect. Camellia in Japan has not been clarified. Therefore, this study aims to understand the evolutionary history of the Japanese sect. Camellia. The genetic population structure was analysed using SNP data and MIG‐seq. The relationship between the Japanese sect. Camellia, including the related species in China, was further inferred from the phylogeny generated by RA x ML, SplitsTree and PCA. Population genetic structure was inferred using a Bayesian clustering method (ADMIXTURE). We subsequently employed approximate Bayesian computation, which was further supported by the coalescent simulations (DIYABC, fastsimcoal and Bayesian Skyline Plots) to explore the changes in population, determining which events appropriately explain the phylogeographical signature. Ecological niche modelling was combined with genetic analyses to compare current and past distributions. The analyses consistently showed that C. japonica and C. rusticana are distinct, having diverged from each other during the Middle to Late Miocene period. Furthermore, C. japonica differentiated into four major populations (North, South, Ryukyu‐Taiwan and Continent). The Japanese sect. Camellia underwent speciation during archipelago formation, reflecting its ancient evolutionary history compared with other native Japanese plants. C. rusticana did not diverge from C. japonica in snow‐rich environments during the Quaternary period. Our results suggest that both species have been independent since ancient times and that ancestral populations of C. japonica have persisted in northern regions. Furthermore, the C. japonica population on the continent is hypothesised to have experienced a reverse‐colonisation event from southern Japan during the late Pleistocene glaciation.